2013
DOI: 10.5812/ijem.8241
|View full text |Cite
|
Sign up to set email alerts
|

Is Hypothyroidism and Hypogonadism an Issue after Aneurysmal Subarachnoid Hemorrhage-An Institutional Experience?

Abstract: BackgroundThe incidence of hypopituitarism in aneurysmal subarachnoid hemorrhage ranges from 0% to 45%. Also the screening for hypopituitarism in survivors of aneurysmal SAH is not a routine. This has led to a controversy in the management of such patients.ObjectivesThe aim of the study was to evaluate the endocrine profile of our patients who had presented with aneurysmal SAH.Patients and MethodsThis was a prospective study conducted over a period of three years in patients of aneurysmal subarachnoid hemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 20 publications
(33 reference statements)
2
18
0
Order By: Relevance
“…Thus, the prevalence obtained from our analysis in the acute phase is higher compared to their results because we included endocrinal dysfunction in the very acute phase of aSAH (including \3 months). Many results from authors who studied both the acute and the chronic phase [10,18,20,44] confirm the improving trend of pituitary dysfunction with time. However, some authors [24,25] reported that new onset of hormone deficiency can occur in the follow up period as well.…”
Section: Prevalence Of Pituitary Dysfunctionmentioning
confidence: 58%
See 1 more Smart Citation
“…Thus, the prevalence obtained from our analysis in the acute phase is higher compared to their results because we included endocrinal dysfunction in the very acute phase of aSAH (including \3 months). Many results from authors who studied both the acute and the chronic phase [10,18,20,44] confirm the improving trend of pituitary dysfunction with time. However, some authors [24,25] reported that new onset of hormone deficiency can occur in the follow up period as well.…”
Section: Prevalence Of Pituitary Dysfunctionmentioning
confidence: 58%
“…Data from the German Interdisciplinary Database including hypopituitarism assessment after 5 months from TBI or SAH, demonstrated [45] a prevalence of any hypopituitarism among SAH patients of 23 % by basal laboratory values which increased up to 32 % in the chronic phase. In many cases [29,39,44], patients were lost at the follow-up and data were incomplete; thus, new-onset of pituitary dysfunction could be even underestimated.…”
Section: Prevalence Of Pituitary Dysfunctionmentioning
confidence: 96%
“…Kronvall et al prospectively analysed 45 patients in the acute phase and 3 to 6 months after SAH, using basal hormonal test and GHRH-arg test for GHD. They did not use a dynamic test to establish ACTH deficiency [ 44 ], Khursheed et al prospectively analyzed 73 patients nine months after SAH for TSH and gonadotropin deficiency and not the other anterior pituitary hormones [ 43 ]. Blijdorp et al prospectively analysed 84 patients and reported preliminary data of 43 patients using basal hormonal tests, synacten test when ACTH deficiency was suspected and a ghrelin test in the early phase after SAH and confirmatory GHRH-arg test after six months [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Blijdorp et al prospectively analysed 84 patients and reported preliminary data of 43 patients using basal hormonal tests, synacten test when ACTH deficiency was suspected and a ghrelin test in the early phase after SAH and confirmatory GHRH-arg test after six months [ 42 ]. The most prominent methodological shortcomings were the incomplete reports of patient selection [ 17 , 32 , 33 , 35 , 37 , 46 ], selection bias [ 17 , 33 - 35 , 42 , 46 ] and inadequate laboratory testing [ 17 , 33 , 35 , 36 , 38 , 43 , 44 ]. Some studies did not use dynamic tests to determine growth hormone or corticotrophin deficiency [ 17 , 34 , 43 , 44 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 34-36, 39, 42, 43, 45, 46] with a total of 705 participants evaluated the prevalence of Gn de ciency that was 0.33 (95% CI, 0.21-0.44, I 2 = 93.4%, P value <0.001). About hyperprolactinemia, the prevalence was 0.12 (95% CI, 0.07-0.16, I 2 = 69.3%, P value = 0.001) calculated by 12 studies [14,19,21,29,34,35,39,42,43,45,46] with a total of 621 participants. As shown in Table 3, it can be seen that the 95% con dence intervals of the prevalence of GHD or Gn de ciency and the remaining ACTH de ciency or hyperprolactinemia have no overlap respectively, so the prevalences of GHD or Gn de ciency were signi cantly higher than that of ACTH de ciency and hyperprolactinemia.…”
Section: Global Analysis For Pdmentioning
confidence: 97%